Entre o silêncio e o acanhamento: o racismo institucional no âmbito dos cursos de formação da magistratura federal entre 2007 e 2019 - Souza, Rodrigo Gonçalves de (2024)
This research aimed to understand how racial issues have been incorporated into the training of federal judges in recent years and in what way the silencing of racial themes has given way to a timid confrontation within the Judiciary. This study seeks to answer the following question: why has the issue of race been silenced for so long in the professional training of judges, and to this day, is it still treated with restraint? To understand why the issue was silenced for so long in the training of judges, the hypothesis worked with was that, despite advances in the black movement, institutional racism persisted within the institutions that make up the justice system until recently. The theoretical support for this investigation relied on a black epistemology, notably in the works of Silvio Almeida, Adilson Moreira, Antônio Sérgio Guimarães, Aparecida Bento, and Nilma Gomes. The categories addressed were individual, institutional, and structural racism, racism as discourse, prejudice, discrimination, and whiteness, as well as other categories such as color, stereotype, stigma, and intersectionality. This study approached racism from a socio-economic perspective, recognizing it as a form of discrimination based on perceived physical and cultural characteristics as inferior or undesirable, spanning from individual manifestations to structural dimensions. It also explored the social construction of race linked to culture and symbolic practices, discussing the relationship with racism and its connection to racial stereotypes. In discussing the relationship between racism and social exclusion, the importance of technically defining prejudice, discrimination, and stigma was emphasized. The underrepresentation of Black individuals in the judiciary was analyzed considering the need for a racial debate in legal education and the impacts of the lack of diversity in the justice system. Methodologically, a bibliographic survey and documentary analysis were conducted (iconographic elements, official quantitative data, economic and social indicators). It is concluded that racism within the Judiciary imposed a prolonged suppression of race in institutional discussions and points to gradual but still limited progress in addressing racial issues, emphasizing the influence of the black movement and the need for more effective anti-racist pedagogical practices and programs. Furthermore, training in racial studies is essential for the judiciary to respond to social tensions and promote racial equality